Prevalence and risk factors of metabolic-associated fatty liver disease during 2014–2018 from three cities of Liaoning Province: an epidemiological survey. Issue 2 (17th February 2022) - Guan, Lin; Zhang, Xinhe; Tian, Haoyu; Jin, Xing; Fan, Hang; Wang, Ningning; Sun, Jing; Li, Dan; Li, Jia; Wang, Xue; Zeng, Zilu; Li, Yiling
Abstract : Objective: To investigate the incidence and characteristics of metabolic-associated fatty liver disease (MAFLD) in individuals undergoing physical examination in Liaoning Province (China). Design: Retrospective study. Setting: Single centre. Participants: Adults who underwent routine health examination at Xikang Medical Center in Liaoning Province (Shenyang, Dandong and Dalian cities) between January 2014 and December 2018. Results: Among the 204 394 included subjects, 71 756 were diagnosed with MAFLD, accounting for 35.28%. The total prevalence of MAFLD in Shenyang, Dandong and Dalian cities over the past 5 years was 35.8%, 40.41% and 31.7%, respectively. Men had a prevalence of 46.12%, which was higher than in women (21.80%). The percentage of MAFLD in body mass index (BMI) <23 kg/m 2 and ≥23 kg/m 2 was 6.49% and 53.23%, respectively. In all subjects, BMI, systolic blood pressure, diastolic blood pressure (DBP), fasting blood glucose (FBG), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), alanine transaminase, aspartate transaminase (AST), alkaline phosphatase (ALP), γ-glutamyl transferase (GGT), blood urea nitrogen, serum creatinine (SCr), serum uric acid (SUA), haematocrit (HCT), mean corpuscular volume (MCV) and urine protein were independently associated with MAFLD (all p<0.001). In lean subjects, DBP, FBG, TG, TC, LDL-C, HDL-C, AST, ALP, GGT, SCr, SUA, HCT and MCV were independently associated with MAFLD (all p<0.001). Conclusion: The prevalence of MAFLD in Liaoning Province was found to be associated with sex, cities with different economic statuses, BMI and multiple metabolic indicators.